Economic Value of Mangrove Forest Ecosystem Damage in Ambon Baguala District Ambon Maluku Indonesia - Revalda Amanda Yacoba Bribka Salakory; Nuddin Harahab; Bagyo Yanuwiadi (Graduate Program, 2018)
This study aims to analyze the level of damage and estimate the economic value of mangrove forest ecosystem damage in Teluk Ambon Baguala District. Data were collected through interviews, documentation, and observation. Method analysis employed was Vegetation Index or NDVI (Normalized Difference Vegetation Index) and economic valuation of damage impact. The result showed that Mangrove forests in Teluk Ambon Baguala district on 2015 were categorized ‘not damaged’ (17.24 Ha) and ‘lightly damaged’ (34.76 Ha). Overall, the economic value of ecosystem services lost due to mangrove forest destruction by water pollution in Teluk Ambon Baguala district. The lost value approximately reached Rp. 3.808.594.100 per year, with the following description: Negeri Passo for Rp. 3,765,838,300 per year, Negeri Lama Village for Rp. 945.627.800 per year and Nania Village for Rp. 650,750,400 per year. A Pigovian taxes were suggested in supporting the conservation of mangrove forest ecosystems and control pollution in Ambon Bay waters.Keyword: Damage, Economic value, Ecosystem, Mangrove forest